#TITLE_ALTERNATIVE# - UTOMO (NIM : 12211071), WAHYU
Differential pressure (ΔP) which is designed (as safety factor) between the hydrostatic pressure of the mud and the formation pressure is also called the overbalance pressure. Due to this pressure difference, permeable rock formations that act as a filter will pass the mud filtrate (filtration loss). This phenomenon will conduct the displacement of formation fluid by the mud filtrate. Mud filtrate invasion will change fluid saturation profiles around the wellbore. The changes in formation water saturation will affect the measurement of logging, especially the resistivity log. The development of the mud filtrate invasion can be modelled using a commercial simulator named Computer Modelling Group (CMG). The model used in this study is a radial vertically heterogeneous reservoir model and using the development model of reservoir Gullfaks Field properties. This method can model the distribution of formation water saturation in three dimensions and estimate the distances of mud filtrate invasion happened. From the model distribution of formation water saturation, using the ArchieÃ‚Â’s equation which is show the relationship between water saturation and resistivity of rock, value of rock resistivity can be calculated for each layer and each radius of the formation. The simulation results show that the approximate distance of mud filtrate invasion and predicted value of rock resistivity, influenced by variations of the density determination errors represented by the differential pressure happened. Besides that, the approximate distance of mud filtrate invasion and estimates value of rock resistivity, also influenced by the physical properties of rocks in a stream of fluid.